The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1976
DOI: 10.1111/j.1399-3054.1976.tb03948.x
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Control of Germination under Saline Conditions of Three Halophytic Taxa in the Genus Suaeda

Abstract: The interaction between hormones and salinity on seed germination of three halophytic taxa in the genus Suaeda: S, maritima (L.) Dum. var. flexilis Focke and var. macrocarpa Moq., and S. depressa (Pursh) Wats, was studied. Exogenous applications of kinetin and gibberellic acid (GA3) were applied in order to determine if either of these growth-promoting hormones would promote germination in the two dormant taxa, Suaeda depressa and S. maritima var. flexilis and to see if osmotically induced dormancy by NaCl cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 14 publications
5
18
0
1
Order By: Relevance
“…The involvement of endogenous gibberellins in A. caudatus seed germination was shown in experiments using an inhibitor of gibberellin biosynthesis (Kępczyński, 1986a). In halophyte species, saline stress inhibited seed germination and reduced gibberellin production (Boucaud and Ungar, 1976). As in other work on inhibition of seed germination (by NaCl) (Białecka and Kępczyński, 2009), in the present study ethephon was more effective than GA 3 in reversing inhibition (by PEG) of A. caudatus seed germination.…”
Section: Discussionsupporting
confidence: 64%
“…The involvement of endogenous gibberellins in A. caudatus seed germination was shown in experiments using an inhibitor of gibberellin biosynthesis (Kępczyński, 1986a). In halophyte species, saline stress inhibited seed germination and reduced gibberellin production (Boucaud and Ungar, 1976). As in other work on inhibition of seed germination (by NaCl) (Białecka and Kępczyński, 2009), in the present study ethephon was more effective than GA 3 in reversing inhibition (by PEG) of A. caudatus seed germination.…”
Section: Discussionsupporting
confidence: 64%
“…GA, mediated stimulation of tube growth may be attributed to its effect on the synthesis of nucleic acids, a amylase and invertase (Mann, 1975). Several reports on the decrease in endogenous cytokinin in plants under saline conditions are available (Itai et at., 1968;Mizrahi et al, 1970Mizrahi et al, , 1972Boucaud & Ungar, 1976). The present study indirectly suggests that pollen responds to substrate salinity in a similar way.…”
Section: Discussionsupporting
confidence: 62%
“…Similarly, under salinity some reports have demonstrated that the endogenous levels and transport of CKs were also reduced in several plant species [77]. Studies with the halophytes Suaea depressa and S. maritima suggested that CKs applications may emphasize the symptoms associated with salt stress [78]. It should be pointed out that this response could be the result of the action of CKs on stimulating stomatal opening, thus facilitating transpiration and therefore magnifying the effect of salinity.…”
Section: Effect Of Ck On Plant Growth Responses Under Drought and Salmentioning
confidence: 99%